PENGARUH STRATEGI OUTDOOR LEARNING BERBASIS EKSPLORASI ALAM TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI DI TAMAN KANAK-KANAK IQRA’ KOTA PADANG - Widia Masrida; Rakimahwati; Farida Mayar; Nenny Mahyuddin (STKIP Subang, 2026)
This study is motivated by the low level of gross motor skills among early childhood students at Taman Kanak-kanak IQRA’ Padang, as indicated by children’s limited ability to perform movements such as running, jumping, throwing, and catching. This problem is caused by the lack of active and engaging learning strategies, as most learning activities are conducted indoors. Therefore, this study aims to determine the effect of outdoor learning strategies based on nature exploration on children's gross motor development. This study employed a quantitative method with a quasi-experimental design using pre-test and post-test in both experimental and control groups. The results showed a significant improvement in the gross motor skills of children in the experimental class compared to the control class. Thus, it can be concluded that outdoor learning strategies based on nature exploration have a significant effect on improving early childhood gross motor skills at Taman Kanak-kanak IQRA’ Padang.